English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

please

2007-10-28 12:32:20 · 2 answers · asked by Anonymous in Science & Mathematics Mathematics

2 answers

a²-b² = (a+b)(a-b)

64x² - 81 = 0
(8x)² - 9² = 0
(8x+9)(8x-9) = 0
x = {-9/8, 9/8}

2007-10-28 12:39:09 · answer #1 · answered by gudspeling 7 · 1 0

Hi,
This is the difference of two squares, and, as you may know, there's a standard formula for that:
a²-b² = (a+b)(a-b)
Let's compare your expression with this:
64x^2-81=0
(8x)²-9² =0
So, a = 8x and b = 9. So, we can just write those twice and connect one set with a minus sign and the other with a positive sign.
(8x-9)(8x+9)=0
Of course, you can solve for the two values of x by solving each factor for x. But since you didn't ask for that, I'll not bore you with a demonstration.

FE

2007-10-28 19:47:08 · answer #2 · answered by formeng 6 · 0 0

fedest.com, questions and answers